Predictors of response to anti‐IL6 monoclonal antibody therapy (siltuximab) in idiopathic multicentric Castleman disease: secondary analyses of phase II clinical trial data. (11th September 2018) - Morra, Deanna E.; Pierson, Sheila K.; Shilling, Dustin; Nemat, Sepideh; Appiani, Carlos; Guilfoyle, Mary; Tendler, Craig; van Rhee, Frits; Fajgenbaum, David C.
Summary: Siltuximab is the only US Food and Drug Administration‐approved treatment for idiopathic multicentric Castleman disease (iMCD), a rare haematological disorder associated with substantial morbidity and mortality. Although siltuximab induces a response in a significant proportion of iMCD patients via interleukin 6 (IL6) neutralization, it is not universally effective. To develop a predictive model of response, we performed an in‐depth analysis of 38 baseline laboratory parameters in iMCD patients from the phase II siltuximab trial who met criteria for treatment response or treatment failure. Univariate analyses identified eight baseline laboratory parameters that were significantly different between responders and treatment failures: albumin, immunoglobulin G (IgG), immunoglobulin A, C reactive protein (CRP), fibrinogen, haemoglobin, sodium and triglycerides. Stepwise logistic regression analysis of these candidate parameters identified a top performing model that included fibrinogen, IgG, haemoglobin and CRP. Based on cross‐validation of the final multivariate logistic regression model, the model accurately discriminated responders from those who failed treatment (area under the receiver operator characteristic curve 0·86, 95% confidence interval: 0·73–0·95). All four laboratory parameters associated with response to siltuximab have biological relationships with IL6 and acute inflammation. Our model suggests that iMCD patients with laboratory evidence of an inflammatory syndrome are the best candidates for siltuximab therapy.